Perempuan Perupa Cina dalam Perubahan Politik di Cina - Ira Adriati Winarno (Journal of Visual Art and Design, 2007)
China has experienced several political changes. The latest change is the emerging of capital-liberalism, which cause their openness to the foreign culture and visitors. This openness has influenced their art work too. The Chinese's Art work is no longer made for propaganda purpose, but shifting to the aspiring of personal expression or for the purpose of social criticism. Yet, seeking the "freedom" of this capital-liberalism era, do not certainly brings equal opportunity to the woman artists of China. It was after the 1995 International Women Conference in Beijing that Chinese women artists began to realize their aspirations. Since then, many works by Chinese woman artists' take woman issues as their object and showing a new expression of aesthetics.